INSECURE ON THE PERSPECTIVE OF TAFSĪR AL-JAYLĀNĪ - Darmawan, Darmawan; Ulfiyaddin, Nuri Fikriyati; Rahmatullah, Salim (Tanzil: Jurnal Studi Al-Quran, 2024)
Insecurity has now become a common thing that affects many people. Many people worry about their future or feel inferior when facing reality or interacting with others. Excessive worry can prevent someone from doing activities or doing something. Insecurity can be a disease that disrupts people's mental health. If not handled well, anxiety, low self-esteem, and feeling unable to accept oneself completely, including feeling inferior, can make someone prefer to be alone and what is most worrying is that when insecurity is not handled well, there is a risk of increasing cases of suicide. Insecurity can be caused by many things, including changes in the environment and times. Materialism results in the loss of the essence of life, which leads to a crisis of meaning, values ​​, and spirituality. Spiritual values ​​can help someone avoid insecurity. A spiritual crisis and mental well-being can trigger emotional anxiety. This research aims to explore the Al-Qur'an's views regarding the phenomenon of insecurity in Tafsīr al-Jaylānī. From an Islamic perspective, the solution to overcoming insecurity includes obedience to Allah, humility, and patience. This research method is qualitative with a character thematic approach. Although al-Jaylānī does not discuss insecurity explicitly, he emphasizes the importance of repentance and returning to spiritual values. The implications of the interpretation show that the Qur'an provides solutions through obedience, patience, and strengthening self-confidence.